Collaborative Technologies and Data Science in Artificial Intelligence Applications - Luther, Wolfram (Logos Verlag Berlin, 2020)
In September 2020, researchers from Armenia, Chile, Germany and Japan met at the American University of Armenia for a virtual conference to discuss technologies with applications in smart cities, data science and information theory approaches for intelligent systems, technical challenges for intelligent environments, smart human centered computing, artificial neural networks, and deep learning. This book presents their contributions to the 2nd CODASSCA workshop on collaborative technologies and data science in artificial intelligence applications, a highly topical issue in today's computer science.